1991
DOI: 10.1095/biolreprod44.3.398
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide is Involved in Hamster Sperm Capacitation in Vitro1

Abstract: We have investigated the possibility that the generation of hydrogen peroxide (H2O2) by spermatozoa plays a physiological role during capacitation. Capacitation is defined as the incubation period required for fertilization in mammals. Capacitation culminates in an exocytotic event, the acrosome reaction (AR). Mammalian sperm generate H2O2 during aerobic incubation and do not contain catalase, the enzyme that promotes scavenging of H2O2. In the present work we show that added catalase inhibited the AR, while g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(66 citation statements)
references
References 0 publications
3
60
0
2
Order By: Relevance
“…9). As the latter specifically scavenges hydrogen peroxide, these data support the notion that this oxidant is a physiological mediator of sperm function, driving both the tyrosine phosphorylation events associated with sperm capacitation (Bize et al 1991, Griveau et al 1994, Rivlin et al 2004, O'Flaherty et al 2006a and facilitating the acrosome reaction (Hsu et al 1999, O'Flaherty et al 2005. It is interesting to note that overall, phenylalanine is a much more powerful stimulus for the acrosome reaction than progesterone.…”
Section: Discussionsupporting
confidence: 68%
“…9). As the latter specifically scavenges hydrogen peroxide, these data support the notion that this oxidant is a physiological mediator of sperm function, driving both the tyrosine phosphorylation events associated with sperm capacitation (Bize et al 1991, Griveau et al 1994, Rivlin et al 2004, O'Flaherty et al 2006a and facilitating the acrosome reaction (Hsu et al 1999, O'Flaherty et al 2005. It is interesting to note that overall, phenylalanine is a much more powerful stimulus for the acrosome reaction than progesterone.…”
Section: Discussionsupporting
confidence: 68%
“…Under these conditions, ROS play key roles in maintaining sperm kinematic and fusigenic functions. A specific ROS, H 2 O 2 , is involved in the hyperactivated movement necessary for spermatozoa to traverse the female genital tract and cumulus cells (Bize et al, 1991). ROS initiate lipid peroxidation, which increases sperm fusigenic func-tions, and which is necessary for binding and traversing the zona pellucida (Aitken et al, 1989).…”
Section: Oxidative Stress Contributes To Abnormal Chromatin Structurementioning
confidence: 99%
“…Because the sperm-oocyte fusion in this test is taken as representative for AR status, ROS seemed to inhibit AR. However, the study of Bize et al [6] suggested that the presence of H,O, (but not superoxide anions) is necessary for AR in hamster sperm, and a recent study of de Lamirande and Gagnon [ 1 11 shows a possible role of ROS (particularly the superoxide anion) in triggering hyperactivation and capacitation of human spermatozoa.…”
Section: Discussionmentioning
confidence: 99%